A coil placement technique to treat intracranial aneurysm with incorporated artery. Issue 3 (March 2018) - Luo, Chao‐Bao; Chang, Feng‐Chi; Lin, Chung‐Jung; Guo, Wan‐Yuo
Abstract : Background: : Endovascular coil embolization is an accepted treatment option for intracranial aneurysms. However, the coiling of aneurysms with an incorporated artery (IA) poses a high risk of IA occlusion. Here we report our experience of endovascular coil placement using a technique that avoids IA occlusion in aneurysms with IAs. Methods: : Over a 6‐year period, 185 patients harboring 206 intracranial aneurysms underwent endosaccular coiling. Forty‐two of these patients with 45 aneurysms were treated by coil placement to avoid IAs occlusion. We assessed the anatomy of the aneurysms and IAs, technical feasibility of the procedure, and degree of aneurysm occlusion. Clinical and angiographic outcomes were assessed as well. Results: : Aneurysms were located in the supra‐clinoid intracranial internal carotid artery (n = 24), anterior cerebral artery (n = 6), middle cerebral artery (n = 7), and vertebrobasilar artery (n = 8). The IA was at the aneurysm neck in 34 patients, body in 10, and dome in 1. Immediate post‐coiling angiogram showed preservation of blood flow through the IA in all aneurysms. Coil compaction with aneurysmal regrowth was found in 7 of 36 patients having follow‐up conventional angiography. One patient had an IA territory infarction after embolization. All 42 patients were followed up (mean: 21 months) and showed no re‐bleeding. Conclusion: : This technique is effective and safe in managing intracranial aneurysms with IAs. Although aneurysmal recurrence may occur in some aneurysms because of insufficient coiling, this technique is simpler to perform and requires less skill than other techniques. It can be an alternative option for treating some selected intracranial aneurysms with IAs.